PENDAMPINGAN KONSELOR BAGI KONSELI HAMIL DI LUAR NIKAH MELALUI CBT, BIBLIOTERAPI, DAN JOURNALING - Durmia Sinta Mawati Tarihoran; Julia Hindradjat (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
Pregnancy outside marriage often produces deep psychological, moral, and spiritual crises accompanied by shame, fear, rejection, and identity confusion. Churches and Christian counselors frequently respond moralistically, failing to address the trauma and cognitive distortions experienced by young women in this situation. This study uses a descriptive qualitative approach through literature review, biblical-theological analysis (Psalm 34:18; John 8:1–11), and a synthesis of Cognitive Behavioral Therapy (CBT), bibliotherapy, and therapeutic journaling within a pastoral counseling framework. The research proposes the Christian Supportive Counseling Model for Crisis Pregnancy (CSCM-CP), consisting of holistic assessment, emotional stabilization, cognitive restructuring, narrative reconstruction through bibliotherapy, journaling for self-integration, and spiritual healing. The study affirms that counselors must function as empathetic companions, not judges, by integrating psychological techniques with Christian values of grace, restoration, and accompaniment